Safety in agricultural work: a documentary review of the regulatory standard 31 - Lima Neto, Inácio Alves de (Brazilian Journal of Production Engineering, 2025)
The agricultural sector is endowed with numerous risk factors. Many of these remain implicit due to the devaluation of rural work. However, since the approval of NR 31 by Ordinance No. 86 of 2005, agricultural work has gained a foundation on the issues of occupational risks related to rural work. Since 2005, until the present year, nine updates have been registered that modified the text of the standard, introducing new parameters to be followed with a view to protecting the worker. Based on this, through documentary research, we sought to analyze the ordinances that updated NR 31 to understand their contributions within the risk management process. At the end of the research, it was possible to attest that the updates to the standard, even if late in some cases, contribute in a highly positive way to the management of risks in the work environment of agricultural workers. The research contributes to new studies focused on safety in agricultural work.